2012
DOI: 10.1177/0733464812450071
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Rurality is not Related to Dementia Caregiver Distress, Burden, and Coping in a Predominantly Rural Sample

Abstract: Earlier research suggests that geographic location matters for informal caregivers of persons with dementia: rural caregivers tend to rely on more informal supports and may report more psychological distress and burden than urban caregivers. Differential access to services may underlie these findings, but degree of rurality is typically measured with population size. In contrast, the current article measured degree of rurality with standardized scale of access to metropolitan centers. In a large sample we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 25 publications
0
33
0
3
Order By: Relevance
“…Approach‐based coping has been associated with higher levels of caregiver resilience and lower levels of caregiver burden, anxiety, and perceived stress . Although previous studies have found that caregivers in urban areas also generally utilize approach‐based coping, it is possible that rural caregivers in our study were more likely to employ it and therefore perceived fewer difficulties related to caregiving than their urban peers. However, we did not have a measure of coping strategy so additional research is needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Approach‐based coping has been associated with higher levels of caregiver resilience and lower levels of caregiver burden, anxiety, and perceived stress . Although previous studies have found that caregivers in urban areas also generally utilize approach‐based coping, it is possible that rural caregivers in our study were more likely to employ it and therefore perceived fewer difficulties related to caregiving than their urban peers. However, we did not have a measure of coping strategy so additional research is needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 64%
“…It is not clear from these data why rural caregivers experienced more burdens but did not perceive difficulty in the caregiving role. Previous research has found that caregivers in rural areas tend to have approach‐based coping strategies, meaning that they face potential stressors directly and use strategies like positive reframing, seeking social support, or problem solving to reduce the negative impact of stressors rather than avoiding them . Approach‐based coping has been associated with higher levels of caregiver resilience and lower levels of caregiver burden, anxiety, and perceived stress .…”
Section: Discussionmentioning
confidence: 99%
“…Dua sırasında tekrarlanan ayetler, meditasyonda olduğu gibi odaklanmayı sağlayarak, bireyin gevşemesine yardım olabilmekte, umut ve iyimserliği de yükseltebilmektedir. [11] Demanslı bireylere bakım verenlerin yaşadığı güçlüklerin araştırıldığı bir çalışmada bakım verenlerin çoğunlukla baş etme yöntemi olarak dua etmeyi tercih ettikleri belirtilmiştir. [10,15] Katılımcılar, bakım verirken yaşadığı zorluklarla başet-me konusunda çoğunlukla aile üyelerinden destek alınması gerektiğini belirtmiştir.…”
Section: Discussionunclassified
“…Bakım vericinin umudunu besleyecek ve destekleyecek hizmetlerin az olması ya da alınamaması bakım vereni zorlayan en önemli faktörlerdendir. [10,11] Bakım verenlerin, bakım aktivitelerini yürütürken aileden destek alamadığı, psikolojik, ekonomik ve aile içi ilişkilerde güçlük yaşadığı, ekonomik durumlarının ve günlük yaşam aktivitelerinin olumsuz etkilendiği bildirilmektedir. [9] Günü-müzde kronik hastalıklarda meydana gelen artışlar, hastaların bakımında ailesine ve bakım verenine düşen sorumlulukları artırmaktadır.…”
Section: Introductionunclassified
See 1 more Smart Citation